2016
DOI: 10.2196/jmir.5461
|View full text |Cite
|
Sign up to set email alerts
|

What Are We Looking for in Computer-Based Learning Interventions in Medical Education? A Systematic Review

Abstract: BackgroundComputer-based learning (CBL) has been widely used in medical education, and reports regarding its usage and effectiveness have ranged broadly. Most work has been done on the effectiveness of CBL approaches versus traditional methods, and little has been done on the comparative effects of CBL versus CBL methodologies. These findings urged other authors to recommend such studies in hopes of improving knowledge about which CBL methods work best in which settings.ObjectiveIn this systematic review, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 129 publications
4
54
0
5
Order By: Relevance
“…It also has to be noted that these static images, even if mentally rotated can only produce an image that is assumed by the learner; however, it can be inaccurate as the mind is filling the gaps of the missing structures (Linn and Petersen, 1985;Liesefeld et al, 2015). With advances in educational technology these traditional resources can be supplemented by interactive multimedia learning tools (Walsh, 2014;Trelease, 2016) and interactive software that can be accompanied with both auditory and visual information (Taveira-Gomes et al, 2016).…”
Section: Supplements Used To Enhance Anatomical Educationmentioning
confidence: 99%
“…It also has to be noted that these static images, even if mentally rotated can only produce an image that is assumed by the learner; however, it can be inaccurate as the mind is filling the gaps of the missing structures (Linn and Petersen, 1985;Liesefeld et al, 2015). With advances in educational technology these traditional resources can be supplemented by interactive multimedia learning tools (Walsh, 2014;Trelease, 2016) and interactive software that can be accompanied with both auditory and visual information (Taveira-Gomes et al, 2016).…”
Section: Supplements Used To Enhance Anatomical Educationmentioning
confidence: 99%
“…Pursuing the same goal, we then conducted a forward search, using Google Scholar to identify studies that cited the included articles. We also consulted the reference lists of 12 earlier reviews and meta-analyses of online and distance education (Cook et al, 2008(Cook et al, , 2010Bernard et al, 2009;Means et al, 2009Means et al, , 2013Martin et al, 2014;Schmid et al, 2014;Liu et al, 2016;Margulieux et al, 2016;Taveira-Gomes et al, 2016;McKinney, 2017;Richmond et al, 2017). This second step of the literature search resulted in another three publications (Harned et al, 2014;Alnabelsi et al, 2015;Olson and McCracken, 2015) that met all the inclusion criteria.…”
Section: Publication Languagementioning
confidence: 99%
“…Chumley-Jones et al (2002) showed that there are few repositories or digital libraries that offer access to e-Learning materials. More recent studies showed that in the last years a higher number of software systems were developed, with a move into a more student-centered model, a focus on implementing reusable software platforms for specific learning contexts, and analysis of online activity to track and predict outcomes (Taveira-Gomes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%